2022
DOI: 10.47941/jep.952
|View full text |Cite
|
Sign up to set email alerts
|

Application and Constraints of Brain-Based Learning in Physics Education

Abstract: Purpose: This paper examines the application of brain-based learning in the teaching of Physics in the selected colleges of education in Oyo State. This study also seeks to identify the constraints and measure the perceptions of both students and teachers in the utilization of brain-based learning models in the teaching of Physics in the selected colleges of education. Methodology: This study adopted a quantitative research methodology in accomplishing the purpose and objectives identified. Multistage sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the meantime, the last stage-celebration and integration-implores all the critical concepts of a love of learning (Farida, 2021) Additionally, the BBL approach can help develop a variety of intelligences, including kinesthetic, logical, musical, intrapersonal, interpersonal, naturalist, verbal, and visual. Summary of Table 2 of scientific studies revealed that the use of the BBL model had an impact on students' learning activities, especially in science subjects at secondary school and tertiary level, carried out by Nwoye et al (2022) and Solomon et al (2022). The BBL model approach is very suitable and preferred by students to be applied in science learning compared to conventional learning (Achor & Gbadamosi, 2020;Saleh & Subramaniam, 2019;Zaqiah et al, 2022).…”
Section: Application Of Brain-based Learningmentioning
confidence: 99%
“…In the meantime, the last stage-celebration and integration-implores all the critical concepts of a love of learning (Farida, 2021) Additionally, the BBL approach can help develop a variety of intelligences, including kinesthetic, logical, musical, intrapersonal, interpersonal, naturalist, verbal, and visual. Summary of Table 2 of scientific studies revealed that the use of the BBL model had an impact on students' learning activities, especially in science subjects at secondary school and tertiary level, carried out by Nwoye et al (2022) and Solomon et al (2022). The BBL model approach is very suitable and preferred by students to be applied in science learning compared to conventional learning (Achor & Gbadamosi, 2020;Saleh & Subramaniam, 2019;Zaqiah et al, 2022).…”
Section: Application Of Brain-based Learningmentioning
confidence: 99%